2006
DOI: 10.1177/154405910608500308
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of CpGs in the Promoter of the COL1A1 Gene in the Aged Periodontal Ligament

Abstract: Although the human periodontal ligament shows age-associated histological alterations, the molecular mechanisms are not yet understood. We previously found that COL1A1 gene expression declines with age. In this study, we asked whether DNA methylation in the regulatory region of the gene alters in the aging process, as a possible cause of the decline. The method used was a bisulfite modification of cytosine and nucleotide sequencing of DNA. While the 1st intron region was kept demethylated at young and old ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…Ohi et al [34] demonstrated that suppression of collagen expression in aged PDLC may be related to DNA hypermethylation of the regulatory region of the type I collagen gene, a mechanism that inhibits gene expression during the aging process of several genes.…”
Section: Discussionmentioning
confidence: 98%
“…Ohi et al [34] demonstrated that suppression of collagen expression in aged PDLC may be related to DNA hypermethylation of the regulatory region of the type I collagen gene, a mechanism that inhibits gene expression during the aging process of several genes.…”
Section: Discussionmentioning
confidence: 98%
“…This is the most abundant protein in the periodontium and maintains the attachment of teeth with the alveolar bone and soft tissues (Bartold et al 2000). It has been observed that type I collagen decreases in the periodontium with increasing age (Ohi et al 2006, Lim et al 2014). This phenomenon was recently reproduced by a study that identified a progressive atrophy of the tooth supporting structures associated with ageing in rats (Leong et al 2012).…”
Section: The Complex Relationship Between Periodontal Tissue Destructmentioning
confidence: 99%
“…It is reasonable to assume that environmental factors, such as exercise, may also work through epigenetic mechanisms to modulate the risk of musculoskeletal soft tissue injuries 9. In support of this, an age-dependent increase in the hypermethylation of the COL1A1 promoter in periodontal ligaments has been reported 60. Future work should therefore consider epigenomic techniques, also within the tissue of interest, such as methylation sequencing and ChIP sequencing, which can be used to identify protein-DNA and protein-RNA interactions.…”
Section: Future Workmentioning
confidence: 94%